2011
DOI: 10.1007/s11136-011-9943-2
|View full text |Cite
|
Sign up to set email alerts
|

Individual interviews and focus groups in patients with rheumatoid arthritis: a comparison of two qualitative methods

Abstract: The method chosen should depend on the objective of the study, issues related to the health condition, and the study's participants. We recommend performing focus groups if the objective of the study is to comprehensively explore the patient perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
107
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(122 citation statements)
references
References 37 publications
8
107
1
6
Order By: Relevance
“…This finding was likely affected by our exclusion of recruitment time in the data collection time calculation. Coenen et al (2012), for example, found that the mean recruitment time for FGs was about 8 times more than for IDIs, which is consistent with the number of additional participants involved.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This finding was likely affected by our exclusion of recruitment time in the data collection time calculation. Coenen et al (2012), for example, found that the mean recruitment time for FGs was about 8 times more than for IDIs, which is consistent with the number of additional participants involved.…”
Section: Discussionsupporting
confidence: 60%
“…While it is a limitation of our analyses that we did not include recruitment time, analysis time, or space rental in our calculations, it would be simple enough for other researchers to add these costs to the equation if they were available for a particular study. We believe that inclusion of these variables would likely further increase FG costs relative to IDI costs, given the additional time and costs associated with FGs in all of these areas (see Coenen, Stamm, Stucki, & Cieza, 2012, for detailed comparisons of time required for FG and IDI activities, including recruitment and analysis). Given these differences, we estimate that our comparative cost-effectiveness calculations are on the conservative side and would expect IDIs, in many contexts, to be even more cost-effective, relative to FGs, than our data indicate.…”
Section: Discussionmentioning
confidence: 99%
“…In previous Core Set projects and ICF research projects, the first three steps of the meaning condensation methodology as described by Kvale (1996) was used (Boonen et al, 2009;Coenen et al, 2012;Coenen et al, 2011;GlĂ€ssel et al, 2011;Gradinger et al, 2011). The essence of that method is the condensation part (i.e.,…”
Section: The Seven-steps Linking Proceduresmentioning
confidence: 99%
“…Firstly, when two consecutive 'units' revealed no new categories and, secondly, when two consecutive 'units' revealed fewer than 5% new categories, with respect to the categories that have already been linked. The 'units' in these studies have usually been focus groups and individual interviews, with saturation generally reached after 5 focus groups and 9 to 12 individual interviews (27,34). However, unlike focus groups or interviews, we were unlikely to obtain the same richness of qualitative information from each participant due to the structure and specificity of our data collection method, a written questionnaire.…”
Section: Linking Concepts To the Icf Established Rulesmentioning
confidence: 99%